Radio Broadcasting as a Component of the Bolshevist System of Authoritary Journalism of Autonomies of the North Caucasus: Stage of Formation (Proceedings of Southern Federal University. Philology, 2020)
During the consolidation of Soviet power in the North Caucasus, the Bolshevik leadership considered broadcasting as the most important tool for introducing Marxist ideology into the consciousness of the mountain masses. This was caused by the fact that the local population was almost completely illiterate and print propaganda was not very effective. Meanwhile, the processes of formation of regional broadcasting are studied only fragmentarily. The article attempts to identify the main trends in the development of North Caucasian radio, to show the evolution of forms and genres of broadcasting, its transformation into the mouthpiece of the Bolshevik authoritarian regime.Key words: history of national broadcasting in the North Caucasus, the role of local radio journalism as a tool for manipulating the mass consciousness of the mountain population.DOI 10.18522/1995-0640-2020-3-215-226